2002
DOI: 10.1021/jp0204105
|View full text |Cite
|
Sign up to set email alerts
|

Role of Crystalline Defects in Electrocatalysis:  Mechanism and Kinetics of CO Adlayer Oxidation on Stepped Platinum Electrodes

Abstract: The kinetics of the electrochemical oxidation of a CO adlayer on Pt[n(111)×(111)] electrodes in 0.5 M H 2 SO 4 has been studied using chronoamperometry. The objective is to elucidate the effect of the crystalline defects on the rate of the reaction by using a series of stepped surfaces. The reaction kinetics of the main oxidative process can be modeled using the mean-field approximation for the Langmuir-Hinshelwood mechanism, implying fast diffusion of adsorbed CO on the Pt[n(111)×( 111)] surfaces under electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

59
513
5
13

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 396 publications
(590 citation statements)
references
References 76 publications
59
513
5
13
Order By: Relevance
“…The species involved in the initial reaction with CO ads is generally regarded to be OH ads formed by the dissociation of 95 adsorbed water 1, 6, 15-17, 29, 35, 48-50 . L-H kinetics are often written such that there is an implicit assumption that any free sites formed in the adlayer will promote the formation of OH ads through rapid spontaneous dissociative oxidative adsorption of bulk water 2,12,[51][52][53][54][55] 49,50,78,79 , it is often considered to be so transient that it is not important 5 . The third step in the oxidation of CO ads is generally ignored and assumed to be extremely fast compared to the first and second, and is implicitly assumed to be via reaction with bulk water to form H 3 O + 5, 49, 80 .…”
Section: Co Reorganisation Compared To Oh Ads Redistributionmentioning
confidence: 99%
See 3 more Smart Citations
“…The species involved in the initial reaction with CO ads is generally regarded to be OH ads formed by the dissociation of 95 adsorbed water 1, 6, 15-17, 29, 35, 48-50 . L-H kinetics are often written such that there is an implicit assumption that any free sites formed in the adlayer will promote the formation of OH ads through rapid spontaneous dissociative oxidative adsorption of bulk water 2,12,[51][52][53][54][55] 49,50,78,79 , it is often considered to be so transient that it is not important 5 . The third step in the oxidation of CO ads is generally ignored and assumed to be extremely fast compared to the first and second, and is implicitly assumed to be via reaction with bulk water to form H 3 O + 5, 49, 80 .…”
Section: Co Reorganisation Compared To Oh Ads Redistributionmentioning
confidence: 99%
“…The nature of this species is somewhat controversial, although Anderson has recently shown through theoretical ab initio charge selfconsistent methods that OH ads should form on a Pt surface at a 10 potential of about 0.6 V. Several investigators claim that OH ads is the species responsible for reacting with adsorbed CO ads , and that this is a chemical Langmuir-Hinshelwood (L-H) reaction [1][2][3][4][5][6][7] . The lowest potentials at which the COOR has been reported is 150 mV for carbon supported platinum 8 , 200 15 mV for a porous platinum electrode 9 and for polycrystalline platinum 10 , and 300 mV for a Pt(111) electrode 11 , and it has been shown that there is a relationship between the number of defects and the activity of the surface 12 . As a result some have suggested that if the L-H mechanism is operative, then 20 the CO ads oxidation activity observed in the hydrogen region implies that OH ads must be present at these potentials 1-9, 11, 13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have revealed that the CO oxidation on Pt(111) and vicinal electrodes takes place according to the mean field Langmuir−Hinselwood (L−H) mechanism [10,11,14,16], in which adsorbed CO reacts with an adsorbed OH species originating from waters' dissociative adsorption. Since the oxidation process takes place at very localized sites where OHads and COads species can interact, the mean field L−H-type mechanism is fulfilled only if CO diffusion on the surface is fast [23].…”
Section: Introductionmentioning
confidence: 99%